“…it's so funny to just throw off the blind girl” subjective experiences of barriers in physical education with visually impaired students—an emancipatory bad practice approach - Martin Giese; Michelle Grenier (Frontiers in Sports and Active Living)
The objective of this study is to examine the subjective barriers experienced by blind and visually impaired students in general physical education (PE) using qualitative research methods. A total of 10 students, comprising six females and four males, between the ages of 17 and 19 (with an average age of 18.5 years) were interviewed. The students had been enrolled in mainstream schools at the International Standard Classification of Education (ISCED) level 2 and had elected to transfer to a boarding school for the visually impaired at the transition to ISCED level 3. In order to gain insight into the reasons behind the decisions to leave general education schooling and attend a boarding school, an emancipatory bad practice approach was employed. The findings indicate that physical education (PE) is a particularly challenging subject area. The assumption that general education practices and placements yield positive outcomes is contradicted by the interviews, which predominantly document negative experiences. In light of these findings, it is imperative that we examine the reasons for exclusion as experienced by marginalized groups in physical education.